Return migration of foreign students and the choice of non-resident tuition fees - Thomas Lange (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
The paper presents a model of student migration in order to determine the optimal choice of non-resident tuition fees in a host country of higher education. Students with rational expectations consider a potential return migration in their first-round decision whether to study abroad, so that demand for the higher education system in the host country and optimal non-resident tuition fees depend on the stay rates of foreign-born graduates.A decline in stay rates of foreign students is demonstrated to induce a cutback of tuition fees if the costs of education per student are not too high. The fact that students take into account the possibility of return migration after graduation in their first-stage location decision in combination with rational expectations finally drives this result.
Keywords: D84; F22; I29; 330; tuition fees; oversea students; return migration; rational expectations; brain drain; preference for foreign lifestyle; Studienfinanzierung; Studierende; Ausländisch; Rationales Verhalten; Internationale Wanderung; Brain Drain